Impact of specialist management on survival from radiation-associated angiosarcoma of the breast. Issue 4 (6th February 2018) - Feinberg, L.; Srinivasan, A.; Singh, J. K.; Parry, M.; Stevenson, J.; Jeys, L.; Grimer, R.; Peart, F.; Warner, R.; Ford, S.; Gourevitch, D.; Hallissey, M.; et al.
Abstract: Background: Radiation-associated angiosarcoma of the breast (RAAS) is a rare complication of adjuvant radiotherapy associated with poor survival. The British Sarcoma Group guidelines recommend that all angiosarcomas are referred to a sarcoma multidisciplinary team, although there is no recommendation that patients are managed within a sarcoma service. The aims of this study were to compare survival, complete excision rates and local recurrence rates of patients managed within a sarcoma service and those managed within local hospitals. Methods: All patients with RAAS referred to a regional sarcoma service between 1998 and 2015 were identified from prospective databases. Patient records, and radiology, pathology and operation notes were reviewed retrospectively. Results: Thirty-six patients were operated on with curative intent; 26 were managed by the sarcoma service (of whom 21 underwent radical excision of the irradiated field followed by chest wall reconstruction) and ten were managed locally. Median age was 69·5 (range 43–85) years. Disease-specific survival was significantly longer in patients managed by the sarcoma service than in those managed locally: median 91·1 (range 69·2–113·0) versus 48·8 (18·6–79·1) months respectively ( P = 0·012). Overall survival rates were similar ( P = 0·112). There was no difference in complete excision rate (18 of 26 in sarcoma service versus 5 of 10 in local services; P = 0·456), although the local recurrence rate was significantly lower among patients managed by the sarcoma service (9 of 26 versus 8 of 10; P = 0·015). Conclusion: Specialist management of RAAS leads to fewer local recurrences and improved disease-specific survival. Early referral and management within specialist units is recommended.